Enrichment of electrotrophic microorganisms from contrasting shallow-sea hydrothermal environments in bioelectrochemical reactors - Carissimo, Antoine; Comes, Victoria; Heussner, Alenica; Prime, Anne-Hélène; Price, Roy E.; Erauso, Gaël; Liebgott, Pierre-Pol; Kerzenmacher, Sven; Pillot, Guillaume (Frontiers in Microbiology, 2025)
IntroductionHydrothermal vents are inhabited by electrotrophic microorganisms, which are capable of oxidizing extracellular compounds, such as metals, to power their metabolisms. However, their diversity is poorly known, especially in shallow-sea hydrothermal vents where it has not been extensively studied. Bioelectrochemical reactors can be used to investigate such electrotrophic diversity by providing an electrode as an electron donor.MethodsHere, a total of 60 different reactors were set up and inoculated with either a microbial community coming from the shallow, acidic (ca. pH 5.5) and hot (ca. 120°C) hydrothermal system of Panarea, Aeolian islands, Italy, or the shallow, alkaline (pH 11) and mild (40°C) hydrothermal system of Prony Bay, New Caledonia.ResultsWith the alkaline sample, no electrical current increase was seen in any of the 15 reactors operated for 6 days under Prony hydrothermal conditions (pH 10, 30–75°C). By contrast, a 6-fold increase on average was observed in reactors operated under the Panarea hydrothermal fluid conditions (pH 4.5–7, 75°C). A Multi-Factor Analysis revealed that the overall bioelectrochemical performances of these reactors set them apart from all the other Panarea and Prony conditions, not only due to their higher current production but also archaeal abundances (measured through qPCR). Most reactors produced organic acids (up to 2.9 mM in 6 days). Still, coulombic efficiencies indicated that this might have been due to the (electro) fermentation of traces of yeast extract in the medium rather than CO2 fixation. Finally, microbial communities were described by 16S metabarcoding and ordination methods, and potential electrotrophic taxa were identified. In Panarea reactors, higher growth was correlated with a few bacterial genera, mainly Bacillus and Pseudoalteromonas, including, for the former, at higher temperatures (55°C and 75°C). In reactors reproducing the Prony Bay hydrothermal conditions, known facultative methylotrophs, such as Sphingomonas and Methylobacterium, were dominant and appeared to consume formate (provided as carbon source) but no electrons from the cathode.ConclusionThese results provide new insights into the distribution and diversity of electrotrophs in shallow-sea hydrothermal vents and allow the identification of potential novel biocatalysts for Microbial Electrosynthesis whereby electricity and carbon dioxide are converted into value-added products.